Enhancing Counseling Services in Secondary Schools Through the Implementation of Training Modules and Counseling Materials for Peer Counselors - Fitriyah, Lailatul (CV. Creative Tugu Pena, 2023)
The implementation of this community service aims to address issues in counseling services in remote secondary schools, resulting from the lack of counselors with a background in counseling education. Counselors often play the role of subject teachers, leading to suboptimal counseling implementation, causing students in need of psychosocial assistance to receive inadequate services. The form of community service utilized combines Service Learning and Community-Based Participatory approaches. Lecturers and students actively engage in developing and implementing training modules and counseling materials for adolescent peer counselors. Meanwhile, the community, particularly secondary schools and peer counselors, are invited to participate in designing and adapting modules to fit the local context and needs. The solution derived from this community service is the development of relevant and effective training modules and counseling materials to enhance the competence of peer counselors in providing support and counseling to their peers. With the existence of these modules, it is anticipated that counseling services in remote secondary schools can be improved, ensuring that students in need of psychosocial assistance are better served. In conclusion, the implementation of this community service combines the Service Learning and Community-Based Participatory approaches to address issues in counseling services in remote secondary schools. The development of training modules and counseling materials emerges as a relevant and effective solution to enhance the quality of counseling services, involving the community as partners in the decision-making process and service implementation. It is expected that this community service will have a positive impact in assisting adolescents in overcoming issues and increasing awareness and social support within the school environment. Keywords: Counseling Services, Peer Counseling, Training Modules, Counseling Materials